Primate gut microbiota induce evolutionarily salient changes in mouse neurodevelopment - Alex R. DeCasien; Jacob E. Aronoff; Elizabeth K. Mallott; Sahana Kuthyar; Sriram Chitta; Brian T. Layden; Maria L. Savo Sardaro; Stanton Gray; Lawrence E. Williams; Emma R. Liechty; Hyo M. Lee; Won Lee; et al. (Proceedings of the National Academy of Sciences, 2026)
Multiple primate species, including humans, evolved brains that are exceptionally large relative to their body sizes. These large brains coevolved with metabolic adaptations that enhance cerebral energy supply, including increased circulating glucose levels. While the gut microbiota (GM) is known to influence host metabolism, its potential role in primate brain evolution remains unclear. To investigate this, we inoculated germ-free mice with the GMs of primate species selected to separate the effects of brain size (encephalization) from phylogenetic relatedness: humans (large-brained, Catarrhini), macaques (smaller-brained, Catarrhini), and squirrel monkeys (large-brained, Platyrrhini). We first show that differences in brain gene expression between mice inoculated with human versus macaque GMs resemble those observed between actual human and macaque brains. Comparing the effects of the different primate GMs on mouse brain gene expression further revealed that despite greater evolutionary distance, the GMs from the two larger-brained species (humans and squirrel monkeys) similarly upregulated genes associated with energy production. Notably, human GMs specifically increased the expression of genes involved in oxidative phosphorylation, and these gene expression changes correlated with increased abundances of GM metabolic pathways related to glucose metabolism and gluconeogenesis. Human GMs also downregulated evolutionarily conserved genes implicated in neurodevelopmental disorders such as autism. Although these are findings based on a small sample of primate species and must be interpreted as preliminary, they suggest that species differences in GM composition can influence brain metabolism and raise the possibility that the GM could have played a supporting role in primate encephalization.